2006
DOI: 10.1634/theoncologist.11-9-1025
|View full text |Cite
|
Sign up to set email alerts
|

Referral to Medical Oncology: A Crucial Step in the Treatment of Older Patients with Stage III Colon Cancer

Abstract: Purpose. Adjuvant chemotherapy for stage III colon cancer produces a substantial survival benefit, but many older patients do not receive chemotherapy. This study examines factors associated with medical oncology consultation and evaluates the impact of such consultation on chemotherapy use.Patients and Methods. We used the Surveillance Epidemiology and End Results-Medicare linked database and identified 7,569 patients, aged 66-99, with stage III colon cancer diagnosed from 1992-1999. Modified Poisson regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
67
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 40 publications
6
67
1
1
Order By: Relevance
“…Few studies have quantified the percentage of patients with stage III colon adenocarcinoma who had a consultation with an oncologist. However, 1 large study conducted in the United States that included patients who were insured under Medicare (patients aged 65 years) indicated that 78% of patients with stage III colon adenocarcinoma had a consultation with a medical oncologist within 6 months of their diagnosis, 22 consistent with our finding of 80%. In that study, factors that were related to consulting with an oncologist included age, race, sex, marital status, year of diagnosis (1992-1999), region of residence, tumor grade, number of positive lymph nodes, comorbidities, and poverty level, 22 similar to our current findings.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies have quantified the percentage of patients with stage III colon adenocarcinoma who had a consultation with an oncologist. However, 1 large study conducted in the United States that included patients who were insured under Medicare (patients aged 65 years) indicated that 78% of patients with stage III colon adenocarcinoma had a consultation with a medical oncologist within 6 months of their diagnosis, 22 consistent with our finding of 80%. In that study, factors that were related to consulting with an oncologist included age, race, sex, marital status, year of diagnosis (1992-1999), region of residence, tumor grade, number of positive lymph nodes, comorbidities, and poverty level, 22 similar to our current findings.…”
Section: Discussionsupporting
confidence: 87%
“…13,20,24 Uneven geographic distribution of medical oncologists was also shown in this study. Nearly one tenth of patients in this study lived in HSAs without medical oncologists, whereas approximately 65% of patients lived in HSAs with Ն nine medical oncologists.…”
Section: Discussionsupporting
confidence: 72%
“…1,5 However, a significant proportion of patients do not receive chemotherapy. [6][7][8][9][10][11][12] Patients who are older, 7,8,10,13 female, 8,14 African American, 9,12,13 and not currently married 9,13 and who live in poverty areas 15 are less likely to receive chemotherapy after colectomy. Being seen by a medical oncologist has also been shown to predict chemotherapy receipt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with other studies, which demonstrated that the decision to get a medical oncology referral is a key step in the eventual receipt of chemotherapy. [37][38][39] From 1992 to 2002, the combination of chemotherapeutic agents also changed. Our results suggest that carboplatin and paclitaxel came into wide use as agents for patients with NSCLC in the U.S.…”
mentioning
confidence: 99%